Determining the morphological characteristics of the young athletics athlete, specializing in distance running, "Beginners category". - benour, Maamar (sports creativity, 2025)
Through the developments witnessed in the science of morphology throughout the ages, and due to the interest of researchers in it, the term "body type" emerged. Currently, most sports are characterized by their own specific morphological type. This type was identified by Sheldon (1940) and named somatotype. He defined it as "the quantitative determination of three components: the first indicates obesity, the second muscularity, and the third leanness" (Mohamed Sobhi Hassanin, 2000). For example, the morphological profile of cyclists is characterized by relatively short lower limbs and a short stature, a wide pelvis, and a muscular profile in the legs and arms. In contrast, middle-distance runners are characterized by short stature, light weight, a short torso, and relatively long lower limbs. This data allows for the evaluation of athletes' physical abilities and level of control, as well as for addressing guidance and selection problems. However, we find few studies that focus on morphological profiles and the physical preparations required for each discipline. Nevertheless, elite sports today are increasingly concerned with understanding and accurately identifying all aspects of the athlete's body, especially its structure. Foreign affairs, where each specialty now requires a specific style and physical preparations that are compatible with the specialty practiced.